Hubungan Attachment Style dengan Loneliness pada Emerging Adulthood yang Sedang Tidak Berpacaran - Fathia Mufida Amalia; Meiske Yunithree Suparman (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Loneliness is a subjective emotional experience commonly observed during emerging adulthood (ages 18–25). In this phase, shifts in emotional and affiliative needs may increase vulnerability to loneliness, particularly in the absence of intimate relationships. One intrapersonal factor influencing loneliness is attachment style, emotional bonding patterns formed in early childhood that shape the quality of interpersonal relationships in adulthood. This study aims to examine the relationship between attachment style and loneliness among emerging adults who are not currently in romantic relationships. A quantitative correlational method was employed using purposive sampling, involving 208 unmarried participants aged 18–25 who were not in romantic relationships. The instruments used were the Indonesian version of the Attachment Style Questionnaire (ASQ) and the UCLA Loneliness Scale Version 3. Spearman correlation analysis revealed a significant negative relationship between secure attachment and loneliness (r = -0.748**, p < 0.01), and a significant positive relationship between fearful attachment and loneliness (r = 0.273**, p < 0.01). No significant associations were found for preoccupied or dismissing attachment styles. These findings highlight the important role of attachment style in shaping loneliness experiences among young adults who are not romantically involved.